The bee balm murders : a Martha's Vineyard mystery - Riggs, Cynthia (Riggs, Cynthia. Martha's Vineyard mysteries., 2011)
When a body is found in the trench where men are laying a fiber-optic cable across Martha's Vineyrd, Victoria Trumbell's new boarder tells her he recognizes the dead man as someone who was a potential investor.